Blast furnace gas carbonyl sulfide low-temperature hydrolysis catalyst and preparation method thereof
By using pickled porous alumina pellets and catalysts with titanium, potassium or sodium as active components, the problem of low temperature activity of existing catalysts is solved, and efficient and low-cost carbonyl sulfur removal is achieved, reducing energy consumption and environmental pollution.
Patent Information
- Application Number
- CN202510381825.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-28
- Publication Date
- 2025-08-08
AI Technical Summary
Existing catalysts have low activity and are prone to inactivation at low temperatures, making it difficult to efficiently remove carbonyl sulfur from blast furnace gas. Traditional methods have problems with high cost, low accuracy or regeneration.
The porous alumina spheres treated with pickling are used as support, combined with titanium, potassium or sodium as active components, and the catalyst is prepared through a vacuum adsorption process to form a high specific surface area and a porous structure to ensure uniform dispersion of the active components.
It improves the adsorption capacity and reaction activity of the catalyst, reduces the activation temperature, significantly improves the low-temperature decomposition efficiency of carbonyl sulfur, and reduces energy consumption and cost.
Smart Images

Figure CN120437995A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field related to catalysts, and in particular to a blast furnace gas carbonyl sulfide low-temperature hydrolysis catalyst and a preparation method thereof. Background Art
[0002] Blast furnace gas (BFG) is a major industrial waste gas generated during the ironmaking process in the steel industry. Its annual emissions are substantial, posing a serious threat to the environment and human health. BFG contains a variety of pollutants, with sulfides being a major concern, particularly carbonyl sulfide (COS). This compound accounts for a high proportion of organic sulfur and, due to its stable chemical properties, is difficult to effectively remove using conventional methods. COS emissions not only cause air pollution but also corrode equipment, impacting the quality and safety of steel products.
[0003] Traditional COS removal methods are primarily categorized as wet and dry methods. Wet removal typically uses an alcohol amine solution or alkaline solution as an absorbent, physically or chemically absorbing COS. However, this method suffers from issues such as high absorbent usage, high costs, and low removal accuracy. Dry removal, on the other hand, relies primarily on adsorbents such as activated carbon, molecular sieves, and metal oxides. While offering advantages such as low cost and simple processes, it presents challenges in terms of adsorption capacity, desulfurization accuracy, and sulfur capacity, as well as the issue of adsorbent regeneration.
[0004] In recent years, catalytic hydrolysis has gained attention due to its advantages, including low energy consumption, operability at room or low temperatures, and the absence of an additional hydrogen source. However, existing catalysts suffer from low activity and susceptibility to deactivation, limiting their widespread industrial application. Therefore, the development of an efficient, low-cost, and long-life low-temperature hydrolysis catalyst is crucial for improving COS removal efficiency, reducing industrial costs, and minimizing environmental pollution. Summary of the Invention
[0005] In order to solve one or more technical problems existing in the prior art, the present invention provides a blast furnace gas carbonyl sulfide low-temperature hydrolysis catalyst and a preparation method thereof.
[0006] The technical solution of the present invention to solve the above technical problems is as follows: a blast furnace gas carbonyl sulfide low-temperature hydrolysis catalyst includes a carrier and an active component, the carrier includes porous alumina balls that have been acid-washed, and the active component includes at least one of titanium, potassium and sodium.
[0007] The present invention has the following beneficial effects: the catalyst utilizes porous alumina beads with a high specific surface area and a porous structure as a carrier, combined with an acid wash activation process, to further enhance the catalyst's adsorption capacity and reactivity. Compared to traditional carriers, the catalyst exhibits higher catalytic efficiency and lower activation temperature.
[0008] On the basis of the above technical solution, the present invention can also be improved as follows.
[0009] Furthermore, the specific surface area of the carrier is greater than 260m 2 / g, the diameter of the porous alumina balls is 3 to 5 mm.
[0010] A method for preparing the above-mentioned blast furnace gas carbonyl sulfide low-temperature hydrolysis catalyst comprises the following steps:
[0011] S1, support activation: acid washing of porous alumina beads;
[0012] S2, impregnation solution preparation: prepare the impregnation solution using tetrabutyl titanate, anhydrous ethanol, potassium hydroxide and sodium hydroxide;
[0013] S3, impregnation solution adsorption: the impregnation solution is evenly dispersed on the porous alumina beads by vacuum adsorption process or liquid phase adsorption process to obtain the initial catalyst sample;
[0014] S4, calcination: drying the initial catalyst sample at a first preset temperature for a first preset time, and then calcining the sample at a second preset temperature for a second preset time to form stable active sites on the porous alumina beads, thereby obtaining a blast furnace gas carbonyl sulfide low-temperature hydrolysis catalyst.
[0015] The beneficial effects of the present invention are as follows: the preparation method of the present invention adopts a vacuum adsorption process, the active components are highly dispersed, no agglomeration occurs, the activity and selectivity of the catalyst are significantly improved, and compared with the traditional impregnation process, the problem of active site blockage due to excessive loading is avoided.
[0016] Furthermore, in S2, the use of tetrabutyl titanate, anhydrous ethanol, potassium hydroxide and sodium hydroxide to prepare an impregnation solution includes: mixing tetrabutyl titanate and anhydrous ethanol and stirring to obtain a sol; adding sodium hydroxide and potassium hydroxide to the ethanol solution and stirring evenly to obtain a mixed solution; placing the mixed solution in an ice water bath and continuing to stir, and dripping the sol to obtain an impregnation solution.
[0017] The beneficial effect of adopting the above further scheme is that the low-temperature synthesis method can effectively control the reaction rate and temperature of the system and ensure the structural stability of the sol. When the sol is added dropwise in an ice-water bath, the lower temperature helps to slow down the rapid gelation of the sol and maintain the structural stability of the sol. Active sites (such as titanium oxygen bonds) can adsorb carbonyl sulfide molecules, reduce the activation energy of COS decomposition at low temperatures, and promote its decomposition by electron transfer or chemical bond breaking. At the same time, the high specific surface area and porous structure can increase the contact area between carbonyl sulfide and the catalyst, thereby further improving the catalytic efficiency at low temperatures. In addition, in industrial applications, low-temperature reactions can significantly reduce energy consumption and save costs. However, in the prior art, many catalysts have low desulfurization efficiency or even fail to work effectively at temperatures below 100°C due to the excessively high activation energy of their active sites at low temperatures and reaction kinetic limitations.
[0018] Furthermore, the ethanol solution is a 90% ethanol solution; the concentration of the sodium hydroxide is 3.5-4.5 mg / mL; and the concentration of the potassium hydroxide is 3-4 mg / mL.
[0019] Furthermore, in S2, tetrabutyl titanate and anhydrous ethanol are mixed at a volume ratio of 1:(3-5).
[0020] Furthermore, in S2, tetrabutyl titanate is mixed with anhydrous ethanol, which includes taking a preset volume of anhydrous ethanol, dropping tetrabutyl titanate into the anhydrous ethanol under stirring, and continuing to stir to obtain a sol.
[0021] Furthermore, in S3, the weight-to-volume ratio of the porous alumina balls to the impregnation solution is 1 g: (11-13) mL.
[0022] Furthermore, in S4, the first preset temperature is 100-130° C., the second preset temperature is 450-600° C., the first preset time is 10-13 hours, and the second preset time is 3-5 hours.
[0023] Furthermore, in S2, the stirring rate is 300 r / min. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The SEM images of the hydrolysis catalysts of Examples 1 to Comparative Example 2 of the present invention are as follows;
[0025] Figure 2 This is an analysis chart of the active component content of the hydrolysis catalysts of Examples 1 to Comparative Example 2 of the present invention;
[0026] Figure 3 This is an enlarged view of the analysis of the active component content of the hydrolysis catalysts of Examples 1 to Comparative Example 2 of the present invention;
[0027] Figure 4aThe BET values of the hydrolysis catalysts of Examples 1 to Comparative Example 2 of the present invention are Figure 1 ;
[0028] Figure 4b The BET values of the hydrolysis catalysts of Examples 1 to Comparative Example 2 of the present invention are Figure 2 ;
[0029] Figure 5 This is an analysis chart of the adsorption performance of COS by the hydrolysis catalysts of Examples 1 to Comparative Example 2 of the present invention;
[0030] Figure 6 This is an analysis chart of the catalytic decomposition performance of COS by the hydrolysis catalysts of Examples 1 to Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0031] The technical solutions of the present invention are described below by means of specific embodiments. It should be understood that the one or more steps mentioned in the present invention do not exclude the presence of other methods and steps before and after the combination step, or that other methods and steps may be inserted between these explicitly mentioned steps. It should also be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. Unless otherwise specified, the numbering of each method step is only for the purpose of identifying each method step, and is not intended to limit the order of arrangement of each method or to define the scope of implementation of the present invention. Changes or adjustments to their relative relationships, without substantial changes in the technical content, may also be considered as the scope of implementation of the present invention.
[0032] The sources of the raw materials and instruments used in the examples are not particularly limited and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0033] Example 1
[0034] The preparation method of the blast furnace gas carbonyl sulfide low-temperature hydrolysis catalyst of the present embodiment comprises the following steps:
[0035] S1, support activation: the porous alumina beads were acid-washed with a 5 wt% to 8 wt% hydrofluoric acid solution for 6 h, and then washed three times with deionized water;
[0036] S2, impregnation solution preparation: prepare the impregnation solution using tetrabutyl titanate, anhydrous ethanol, potassium hydroxide and sodium hydroxide;
[0037] Specifically, tetrabutyl titanate and anhydrous ethanol are mixed in a ratio of 1:4 to prepare a sol. 16.8 ml of anhydrous ethanol is added dropwise with stirring at 300 r / min, and stirring is continued for 30 min to obtain a sol. 90 ml of anhydrous ethanol is added with stirring at 300 r / min, 10 ml of deionized water is added, 0.36 g of potassium hydroxide, and 0.39 g of sodium hydroxide are added, and stirring is continued at room temperature for 1 h. Stirring is continued in an ice-water bath, and the sol is slowly added dropwise to obtain an impregnation solution.
[0038] S3, impregnation solution adsorption: Using a vacuum adsorption process, the stirred impregnation solution and 10g of alumina balls are placed in a vacuum drying oven, and the porous alumina balls adsorb the impregnation solution at room temperature; the impregnation solution is evenly dispersed on the porous alumina balls to obtain a primary catalyst sample;
[0039] S4, calcination: the sample after rotary evaporation was placed in a 120°C oven for constant temperature drying for 12 hours. The dried sample was calcined in a muffle furnace at 500°C for 4 hours to form stable active sites on the porous alumina beads, thereby obtaining a blast furnace gas carbonyl sulfide low-temperature hydrolysis catalyst.
[0040] The ICP, BET, COS adsorption and catalytic performance tests of the blast furnace gas carbonyl sulfide low-temperature hydrolysis catalyst obtained in this example and the following examples were all conducted in accordance with standard tests.
[0041] in, Figure 2 and Figure 3 The ICP results of the blast furnace gas carbonyl sulfide low-temperature hydrolysis catalyst obtained in Example 1, Comparative Example 1, and Comparative Example 2 and the old original carrier (porous alumina beads that have not been activated, impregnated, or calcined) are shown. Figure 2 and Figure 3 The horizontal axis is the sample type, and the vertical axis is the metal ion content of the sample; Figure 4a The specific surface area results of the blast furnace gas carbonyl sulfide low temperature hydrolysis catalyst were obtained for Example 1, Comparative Example 1, and Comparative Example 2. The horizontal axis is the relative pressure, which indicates the adsorption state of the catalyst sample at different pressures. The vertical axis is the adsorption amount (Quantity Adsorbed), and the unit is the adsorption volume (cm2) per gram of sample under standard conditions. 3 / g STP), which represents the amount of gas adsorbed by the sample at different relative pressures; Figure 4b The horizontal axis is the pore diameter (Pore Diameter), the unit is nanometer (nm), which represents the size of the pores in the catalyst sample, and the vertical axis is the differential of the pore volume distribution (dV / dlog(D)), the unit is volume per gram of sample (cm 3 / g), indicating the proportion of pores with different pore sizes in the sample; Figure 5Shown is an adsorption isotherm graph showing the adsorption capacity of COS for the blast furnace gas carbonyl sulfide low-temperature hydrolysis catalysts obtained in Example 1, Comparative Example 1, and Comparative Example 2, and the old original support. The horizontal axis is temperature (°C), and the vertical axis is adsorption capacity (uV). Figure 6 The effect of the blast furnace gas carbonyl sulfide low-temperature hydrolysis catalyst obtained in Example 1 to Comparative Example 2 on the catalytic decomposition performance of COS is shown in Figure 1. The horizontal axis is temperature in degrees Celsius (°C), and the vertical axis is decomposition rate in percentage (%), which represents the efficiency of COS decomposition.
[0042] The surface active components of the catalyst for low-temperature hydrolysis of carbonyl sulfide from blast furnace gas prepared in Example 1 are uniformly and densely dispersed to form a porous structure without agglomeration (e.g., Figure 1 The catalytic active components (sodium potassium titanium) have the highest content (as shown in the attached Figure 2 and Figure 3 Specific surface area is as high as 269.7437m 2 / g, and the mesoporous structure is obvious (such as the attached Figure 4a and Figure 4b In the high temperature section and the low temperature section, the adsorption capacity of COS is higher (as shown in the attached Figure 5 It has excellent COS catalytic activity in a wide temperature range, especially at lower temperatures, it exhibits efficient COS decomposition ability (as shown in the attached Figure 6 The decomposition efficiency is as high as 96.59% at 100°C, further increased to 97.9% at 125°C, and even reached a high decomposition efficiency of 99.1% at 150°C.
[0043] Comparative Example 1
[0044] The blast furnace gas carbonyl sulfide low-temperature hydrolysis catalyst of this comparative example was prepared by circulating the vacuum adsorption impregnation solution twice, and the remaining steps were the same as those of Example 1.
[0045] The surface active components of the obtained blast furnace gas carbonyl sulfide low temperature hydrolysis catalyst are agglomerated and the pore structure is covered (such as the attached Figure 1 As shown), the content of catalytically active components is low (as shown in the attached Figure 2 and Figure 3 Specific surface area: 142.2875m 2 / g(if attached Figure 4a and Figure 4b As shown), in the low temperature section, they all showed the ability to adsorb COS (as shown in the attached Figure 5 The catalytic efficiency of COS is less than 20% (see Figure 6 shown).
[0046] Comparative Example 2
[0047] The blast furnace gas carbonyl sulfide low-temperature hydrolysis catalyst of this comparative example was prepared by circulating the vacuum adsorption impregnation solution three times, and the remaining steps were the same as those of Example 1.
[0048] The surface active components of the obtained blast furnace gas carbonyl sulfide low temperature hydrolysis catalyst are agglomerated and the pore structure is covered (such as the attached Figure 1 As shown), the content of catalytically active components is low (as shown in the attached Figure 2 and Figure 3 Specific surface area: 133.0190m 2 / g(if attached Figure 4a and Figure 4b As shown), the adsorption capacity for COS is poor (as shown in the attached Figure 5 The catalytic efficiency of COS is less than 20% (see Figure 6 shown).
[0049] While vacuum adsorption can facilitate the entry of the catalyst into the pores of the alumina spheres, thereby increasing the contact area between the catalyst and the reactants and enhancing catalytic activity, as the number of adsorption cycles increases, the catalyst particles may gradually accumulate and clog the pores, resulting in a decrease in the catalyst's effective active sites and, in turn, a reduction in its catalytic efficiency for the decomposition of carbonyl sulfide (COS).
[0050] Comparative Example 3
[0051] The blast furnace gas carbonyl sulfide low-temperature hydrolysis catalyst of this comparative example is loaded with an impregnation liquid by a liquid phase adsorption method. The impregnation liquid and 10 g of porous alumina beads are mixed, heated and stirred at 70° C. until the solvent evaporates, and the porous alumina beads adsorb the impregnation liquid at room temperature. The remaining steps are the same as those in Example 1.
[0052] The resulting hydrolysis catalyst's catalytic efficiency for COS is weaker than that prepared by vacuum adsorption. This is because the slower molecular diffusion in the liquid phase slows the rate at which the target substance reaches the surface of the alumina beads. Under vacuum conditions, molecular diffusion resistance is low, allowing the target molecules to quickly reach the adsorption sites on the alumina beads.
[0053] Comparative Example 4
[0054] The catalyst for low-temperature hydrolysis of carbonyl sulfide from blast furnace gas in this comparative example was prepared using alumina pellets that had not been acid-washed and activated, and the remaining steps were the same as those in Example 1.
[0055] Alumina pellets that have not been acid-washed and activated do not have adequately optimized pore structures, which prevents them from providing sufficient attachment sites for active components. Consequently, the content of catalytically active components loaded on their surfaces is extremely low, with the titanium active component content being less than 0.05 wt%. This low content of active components limits the catalyst's performance in the catalytic decomposition of carbonyl sulfide (COS). Within the temperature range of 75°C to 200°C, the catalytic decomposition rate is less than 5%, making it difficult to meet the practical requirements for efficient COS removal.
[0056] The above results show that the optimization of pore structure is necessary to improve the performance of the catalyst. Through acid washing, activation and pore expansion treatment, the loading amount and dispersion of active components are increased, thereby enhancing the catalytic performance of the catalyst.
[0057] Comparative Example 5
[0058] In this embodiment, the blast furnace gas carbonyl sulfide low-temperature hydrolysis catalyst uses a high-temperature oil bath to prepare the impregnation solution. Specifically, the ethanol mixed solution is placed in an 80°C oil bath and stirred, and the sol is dropped into it to obtain the impregnation solution. The remaining steps are the same as those in Example 1.
[0059] Under high temperature conditions, the structural stability of the titanium sol is destroyed, resulting in an extremely low, almost undetectable loading of the active component titanium in the final alumina spheres. Due to the insufficient active component content, the catalyst's catalytic decomposition rate of carbonyl sulfide decreases to only 2% within the temperature range of 75°C to 200°C. This phenomenon demonstrates that low temperature conditions effectively maintain the structural integrity of the titanium sol, providing a mild loading environment and improving the catalyst's catalytic performance.
[0060] The above examples are merely descriptions of specific embodiments of the present invention and do not limit the scope of the present invention. Those skilled in the art may make various modifications and changes based on the existing technology. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary engineering technicians in this field should fall within the scope of protection determined by the claims of the present invention.
Claims
1. A catalyst for the low-temperature hydrolysis of carbonyl sulfide from blast furnace gas, characterized in that: The invention comprises a carrier and an active component. The carrier comprises porous alumina balls which have been subjected to acid washing treatment. The active component comprises at least one of titanium, potassium and sodium.
2. The catalyst for low-temperature hydrolysis of carbonyl sulfide from blast furnace gas according to claim 1, characterized in that: The specific surface area of the carrier is greater than 260m 2 / g, the diameter of the porous alumina balls is 3 to 5 mm.
3. A method for preparing the blast furnace gas carbonyl sulfide low-temperature hydrolysis catalyst according to claim 1 or 2, characterized in that: The following steps are involved: S1, support activation: acid washing of porous alumina beads; S2, impregnation solution preparation: prepare the impregnation solution using tetrabutyl titanate, anhydrous ethanol, potassium hydroxide and sodium hydroxide; S3, impregnation solution adsorption: The impregnation solution is evenly dispersed on the porous alumina beads by vacuum adsorption or liquid phase adsorption to obtain the initial catalyst sample; S4, calcination: drying the initial catalyst sample at a first preset temperature for a first preset time, and then calcining the sample at a second preset temperature for a second preset time to form stable active sites on the porous alumina beads, thereby obtaining a blast furnace gas carbonyl sulfide low-temperature hydrolysis catalyst.
4. The preparation method according to claim 3, characterized in that In S2, the use of tetrabutyl titanate, anhydrous ethanol, potassium hydroxide and sodium hydroxide to prepare an impregnation solution includes: mixing tetrabutyl titanate and anhydrous ethanol and stirring to obtain a sol; adding sodium hydroxide and potassium hydroxide to the ethanol solution and stirring evenly to obtain a mixed solution; placing the mixed solution in an ice water bath and continuing to stir, and dripping the sol to obtain an impregnation solution.
5. The preparation method according to claim 4, characterized in that: The ethanol solution is a 90% ethanol solution; the concentration of the sodium hydroxide is 3.5-4.5 mg / mL; and the concentration of the potassium hydroxide is 3-4 mg / mL.
6. The preparation method according to claim 4, characterized in that: In S2, tetrabutyl titanate and anhydrous ethanol are mixed at a volume ratio of 1:(3-5).
7. The preparation method according to claim 4, characterized in that: In S2, tetrabutyl titanate is mixed with anhydrous ethanol, which includes taking a preset volume of anhydrous ethanol, dropping tetrabutyl titanate into the anhydrous ethanol under stirring, and continuing to stir to obtain a sol.
8. The preparation method according to claim 3, characterized in that: In S3, the weight-to-volume ratio of the porous alumina beads to the impregnation solution is 1 g: (11-13) mL.
9. The preparation method according to claim 3, characterized in that: In S4, the first preset temperature is 100-130°C, the second preset temperature is 450-600°C, the first preset time is 10-13 hours, and the second preset time is 3-5 hours.
10. The preparation method according to claim 4, characterized in that: In S2, the stirring rate is 300 r / min.